Epstein Barr Virus in Hodgkin’s Lymphoma a Path Less Treaded: An Observational Study - Balhara, Kirti; Singh, Sarika; Jain, Shyamlata; Daga, M K; Vindal, Anubhav (Annals of Pathology and Laboratory Medicine, 2020)
Background: Epstein-Barr virus (EBV) is a ubiquitous virus belonging to γ-Herpesvirus subfamily, infecting B cells, T cells, Natural killer (NK) cells & causes both benign and malignant diseases. It has been detected in large subset of Hodgkin lymphoma (HL) cases around the world, especially in countries with poor socioeconomic conditions and among younger age. Limited studies are available reflecting the Indian scenario of HL and EBV association. EBV positivity in Indian HL varies from 28-97% Majority of these studies employed Immunohistochemistry (IHC) for LMP1, a few performed In Situ Hybridisation (ISH) for EBER. Objective: To study the association of EBV in classical HL by immunohistochemical expression of latent membrane protein 1 (LMP1) antigen in North Indian population and to correlate it with different demographic variables & subtypes of HL. Materials and Methods: Observational study including 26 untreated HL cases diagnosed on lymph node excision biopsy. IHC was performed for EBV LMP1, CD15, CD30, CD45, CD3, CD20. Results: Patients ranged in age from 5-55years (median 18yrs), with M:F ratio of 3.3:1. Palpable lymphadenopathy was found in all cases followed by pallor (64%), B symptoms (50%), nodal pain (30.8%) & bulky disease (19.2%). Maximum number of patients were in Stage I (65.4%) followed by stage II&III (15.4% each) & stage IV (3.8%). Mixed cellularity HL comprised 77%, lymphocyte depleted 11.5%, nodular sclerosis 7.7% & lymphocyte rich 3.8%. IHC for EBV LMP1 was positive in 73.1% cases. Mixed cellularity HL showed an association in 70% cases. Conclusions: HL in India is a disease of young males, with mixed cellularity as the commonest subtype, highly associated with EBV and presentation at an early stage.